2016
DOI: 10.1371/journal.pone.0163156
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide Survey of Knowledge and Health Beliefs regarding Human Papillomavirus among HPV-Vaccinated Female Students in Malaysia

Abstract: The National HPV Immunization Programme, which offers free human papillomavirus (HPV) vaccines to teenaged female students, was launched in Malaysia in 2010. HPV vaccination paired with adequate knowledge about HPV infection provides the best protection against cervical cancer. To identify the level of knowledge and the health beliefs towards HPV and the HPV vaccine among HPV-vaccinated female students in Malaysia. A nationwide cross-sectional survey among 14 years old female students who had received three do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…However, several countries also offer the vaccine to boys to ensure their direct and immediate protection from genital warts and forms of HPV-related cancer that affect both men and women [15]. In addition, the results are consistent with a study in which the majority of respondents were unaware that vaccinating boys with HPV can help protect girls against HPV infection [7].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…However, several countries also offer the vaccine to boys to ensure their direct and immediate protection from genital warts and forms of HPV-related cancer that affect both men and women [15]. In addition, the results are consistent with a study in which the majority of respondents were unaware that vaccinating boys with HPV can help protect girls against HPV infection [7].…”
Section: Discussionsupporting
confidence: 79%
“…Therefore, it is essential to increase the knowledge and awareness of health risks regarding HPV infection among teenage girls who have received the HPV vaccine [7].…”
Section: Introductionmentioning
confidence: 99%
“…With the urban lifestyle, internet seemed to be their second of source to obtain HPV-related information (16.8%). It appears that socio-demographical backgrounds contrasting previous studies conducted in rural area, as they claimed that internet was one of the least informative sources about HPV and its vaccine (Rashwan et al, 2011;Wong et al, 2016). Hence, a short interactive and informative video can be disseminated to attract more awareness in the urban setting while a school-based visits by the health enforcement could be directed in the rural area.…”
Section: Discussionmentioning
confidence: 96%
“…Hence, one may voice out a suggestion to the government to subsidise the vaccine price for those who are self-aware yet ineligible individuals. Interestingly, a shift in study population revealed that secondary-school students refused the vaccine due to its delivery profile (intramuscular) which is too painful and inconvenient follow-ups (Wong et al, 2016). Pricing was found to be their least concern as they are the main target of government programme.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation